2009
DOI: 10.1093/aje/kwp211
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Early Pregnancy and Risk of Preterm Birth

Abstract: The authors determined the association between metabolic syndrome in early pregnancy (mean, 11.96 weeks) and the risk of preterm birth in the mother-child cohort study ("Rhea" Study) in Crete, Greece, 2007-2009. Maternal fasting serum samples were collected, and blood pressure was measured at the time of the first major ultrasound examination (n = 625). Multivariable log-binomial regression models were used. Women with metabolic syndrome were at high risk for preterm birth (relative risk (RR) = 2.93, 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 171 publications
(179 citation statements)
references
References 31 publications
6
167
4
2
Order By: Relevance
“…This incidence of preterm deliveries is supported by study done by Chatzi et al, where they found a strong association between development of metabolic syndrome and subsequent preterm delivery. 14 In the present study, 72 (72%) patients had normal delivery, 04 (04%) patients had instrumental delivery and 24 (24%) had caesarean delivery. In glibenclamide group 34 (68%) patients had normal delivery, 04 (08%) patients had instrumental delivery and 12 (24%) patients had caesarean delivery, whereas in insulin group 38 (76%) patients had normal delivery and 12 (24%) patients had caesarean delivery.…”
Section: Discussionsupporting
confidence: 42%
“…This incidence of preterm deliveries is supported by study done by Chatzi et al, where they found a strong association between development of metabolic syndrome and subsequent preterm delivery. 14 In the present study, 72 (72%) patients had normal delivery, 04 (04%) patients had instrumental delivery and 24 (24%) had caesarean delivery. In glibenclamide group 34 (68%) patients had normal delivery, 04 (08%) patients had instrumental delivery and 12 (24%) patients had caesarean delivery, whereas in insulin group 38 (76%) patients had normal delivery and 12 (24%) patients had caesarean delivery.…”
Section: Discussionsupporting
confidence: 42%
“…* Totals may not add up to 75 because of missing values.† Represents a test for linear trend with the exception of sex, smoking habits and breastfeeding duration (Wald test).‡ According to the IOM 2009 gestational weight gain guidelines 12.§ Based on internally standardized percentile values as previously described 4.¶ According to the World Health Organization growth reference 6, 7, 8. For both BMI and height, the ‘<1 z‐score’ category includes one child with z‐score <−2.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of the study population have been described elsewhere (16) . A random sample of 828 mothers were contacted by telephone at the 18 months follow-up and 599 (72 %) agreed to participate in the neurodevelopmental assessment (17) .…”
Section: Study Populationmentioning
confidence: 99%